The very busy spider - Carle, Eric, 1929-2021 (London Puffin Books, Penguin Random House, 2009)
Early one morning a little spider begins to spin her web on a fencepost. In this multi-sensory book, children can feel the pictures aswell as see them, while they hear or read the easy rhythmic text.Alongside the visual excitement of Eric Carle's vibrant collages offamiliar animals is the tactile experience of feeling the spider's webas it grows from a simple line into a complex and beautiful creation -a perfect story for reading aloud and sharing.Eric Carle is an internationally bestselling and award-winning author and illustrator of books for very young children. Eric lives in Massachusetts with his wife, Barbara. The Carles opened The Eric Carle Museum of Picture Book Art in Massachusetts in 2002.
Keywords: anglické rozprávky; publikácie pre deti; leporelá; čítame si spolu 0+; cudzojazyčná literatúra